2017
DOI: 10.1038/srep45115
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian Gland Dysfunction Correlates to the Tear Film Instability and Ocular Discomfort in Patients with Pterygium

Abstract: Pterygium is a very common disease in an eye clinic characterized by a benign proliferation of local conjunctiva that often crosses the limber of cornea and extends into corneal surface. Variety of studies has showed that pterygium is able to result in ocular discomfort and the change of ocular surface environment, such as dry eye. However, the link between abnormal tear film function and pterygium is controversial. Meibomian gland dysfunction (MGD) is a common cause of dry eye and ocular discomfort but is oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
7
28
0
Order By: Relevance
“…This study reported NIBUT, meibomian gland dropout and meibum score alterations in pterygium patients. [9] However, besides these findings, by evaluating each patient meibography picture, an association of the dropout area related to the topography of the pterygium was observed in a considered number of cases, to our knowledge, no association with pterygium localization was described before. [23]…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This study reported NIBUT, meibomian gland dropout and meibum score alterations in pterygium patients. [9] However, besides these findings, by evaluating each patient meibography picture, an association of the dropout area related to the topography of the pterygium was observed in a considered number of cases, to our knowledge, no association with pterygium localization was described before. [23]…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have pointed to tear film and ocular surface varying changes related to pterygium, but consistent correlations remain unknown. [69] Although numerous theories have been listed in the pathogenesis of the pterygium (e.g. exposure to ultraviolet radiation, viral infection, oxidative stress, genetic problems, inflammatory mediators, extracellular matrix modulators) the mechanism responsible development remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have pointed tear film and ocular surface changes related to pterygium, but consistent correlations remain unknown. [69] Although numerous theories have been implicated in pterygium pathogenesis, including ultraviolet radiation exposure, viral infection, oxidative stress, genetic issues, inflammatory mediators, extracellular matrix modulators, it remains controversial as well as its impact on ocular surface homeostasis and function. [10] And a better understanding of the pathophysiological mechanisms associated with pterygium, the morphological alterations on the ocular surface and functional impact may contribute to specific approaches and more effective therapeutic proposals for this common ocular condition.…”
Section: Introductionmentioning
confidence: 99%
“…1. Meibomian gland expression (MG expressibility) was scored according to the secretion seen in all 5 meibomian glands [20] : 0, all glands; 1 (3–4 glands); 2 (1–2 glands); and 3 (no glands). Meibum quality (Meibum score) was graded as follows [21] : 0 (clear); 1 (cloudy); 2 (cloudy with debris); 3 (inspissated, toothpaste-like).…”
Section: Methodsmentioning
confidence: 99%